SURVEY SARANA DAN PRASANA OLAHRGA DI SMA SE- ACEH BESAR - Husaini Husaini; Muhammad Muhammad (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
Sports facilities and infrastructure in schools in Indonesia still do not receive special attention from the government and society. Sports facilities and infrastructure in all public high schools in Aceh Besar have not been properly surveyed, so that the need for sports facilities and infrastructure in each school is not met with certainty. This study aims to determine the existence and condition of sports facilities and infrastructure in SMA Negeri Aceh Besar in the 2014/2015 academic year. The approach in this research uses a qualitative descriptive approach with the type of evaluation. The population in this study amounted to 28 public high schools, and the sample in this study amounted to 18 public high schools. Data collection techniques used in this study were interviews and observations. The results of the data analysis show that: In all SMA Negeri Aceh Besar there is not a single public SMA that meets the standard of use or completeness of sports facilities and infrastructure. There are 141 sports facilities and infrastructure that are not available in SMA Negeri Aceh Besar, including: sports facilities totaling 79 types and sports infrastructure totaling 62 types. Sports facilities and infrastructure that are lacking in SMA Negeri Aceh Besar are 471 types, including sport facilities totaling 263 types and sports infrastructure totaling 208 types. The condition of sports facilities and infrastructure in SMA Negeri Aceh Besar is generally not good. It is hoped that the Aceh Besar Government will be able to complete sports facilities and infrastructure in schools, in realizing outstanding students in school-level sports events at the same level.